Islamic Parenting di Panti Asuhan Songkhla Thailand : (Studi Pola Asuh di Lembaga Santiwit, Chana Songkhla Thailand) (Jurusan Bimbingan dan Konseling Islam, 2017)
focus of this research is (1) What is the process of Islamic Parenting (Islamic parenting) at the Santiwit institution, Chana Songkhla Thailand (2) What is the outcome of Islamic Parenting (Islamic parenting) at the Santiwit institution, Chana Songkhla Thailand In answering these problems, this study uses descriptive qualitative methods, namely by describing what was studied. Qualitative data were obtained from interviews, observations, and documentation. Interviews were conducted by the author with foster parents and foster children regarding Islamic parenting that was applied as well as the results of Islamic parenting. The author made observations to observe the results of Islamic parenting shown by the attitude of foster children. The documentation is done by the writer in every activity to find out the forms of Islamic parenting that are applied. The results of this study indicate that Islamic parenting at the Santiwit institute, Chana Songkhla Thailand includes several aspects, namely aspects of psychological and mental education, religious education and religious spirit, moral and social education, and beauty education (aesthetics). The aspects of psychological and mental education that is by giving gifts to foster children who excel, checking schoolwork (homework) by foster parents, and providing life motivation. Faith education and religious enthusiasm that is by praying five times in congregation, reading the letter of yasin, reciting the Qur'an, majlis shalawat, teaching of Islamic sciences (Tadika). Social and social education is by eating together in an orphanage canteen, giving school allowances and compensation by the owner of the Santiwit institution. Beauty education (aesthetics), namely by performing nasyid in certain events, and room cleanliness programs. The success rate of the Islamic parenting process in all aspects reaches 70%.